Trends in polymers networks applied to the removal of aqueous pollutants: A review - Baigorria, Estefanía [UNESP]; Galhardi, Juliana A. [UNESP]; Fraceto, Leonardo F. [UNESP] (Elsevier, 2021)
The contamination of aqueous systems is of global concern. It is extensively known that contaminants of organic, inorganic, and microbiological origin adversely affect water basins, causing environmental damages and numerous human health problems. Polymer networks or hydrogels have been successfully applied as a technology for the removal of aqueous contaminants from effluents and wastewaters. The present review brings different polymeric network materials (nano- and micro-materials) applied for aqueous pollutant removal. Different types of pollutants are included, including toxic metals, dyestuffs, pesticides, herbicides, phenolic compounds, organic matter and microorganisms. In addition, a holistic view of published patents involving hydrogels for different applications is presented, as well as current products on the market.
Keywords: Aqueous pollutants; Hydrogel; Polymeric compounds; Polymeric network; Water pollution; Water remediation